Mutations in the Promoter and Coding Regions of Avr3a Cause Gain of Virulence of Phytophthora sojae to Rps3a in Soybean - Hu, Yanhong; He, Zhihua; Kang, Yebin; Cui, Linkai (Frontiers in Microbiology, 2021)
Phytophthora sojae threatens soybean production worldwide, and the cultivation of soybean cultivars carrying Rps genes is the most effective way to control this pathogen. However, DNA mutations in the Avr genes of P. sojae can make it escape recognization of the corresponding Rps genes, leading to the loss of soybean resistance. In this study, we investigated sequence polymorphism and transcript level of the Avr3a gene in Chinese isolates of P. sojae. Twenty-four mutations resulting in five unique Avr3a alleles were discovered in the Avr3a coding region from 32 P. sojae isolates. The Avr3a transcripts were detectable in the isolates containing Avr3a(I), Avr3a(II), Avr3a(III), and Avr3a(IV), but not in the isolates containing Avr3a(V). Promoter and 5'-UTR sequence analysis revealed eight unique mutations in the promoter region of Avr3a(V), suggesting that the mutations could result in the loss of Avr3a(V) transcription. Virulence tests indicated the isolates containing Avr3a(II) and Avr3a(IV) were virulent, suggesting that the mutations in the coding regions of Avr3a(II) and Avr3a(IV) caused the gain of virulence to Rps3a. Based on DNA mutations of Avr3a in virulent alleles, two SNP markers and one PCR-based marker were developed successfully for detecting the virulence of P. sojae isolates to Rps3a. These findings provide new insights into escape mechanisms of Avr3a and effective support for accurate pathotype identification of P. sojae using molecular methods.